Comparative analysis of proteomes and transcriptomes revealed the molecular mechanism of development and nutrition of Pleurotus giganteus at different fruiting body development stages - Yu, Hailong; Jiang, Ning; Yan, Miaomiao; Cheng, Xuan; Zhang, Lujun; Zhai, Dandan; Liu, Jianyu; Zhang, Meiyan; Song, Chunyan; Yu, Hao; Li, Qiaozhen (Frontiers in Nutrition, 2023)
Pleurotus giganteus is a commercially cultivated high-temperature mushroom. Investigating the molecular mechanism of fruiting body development will help us to better understand the regulation of substrates and energy in this process. However, little information has been reported on the development and nutrients of the P. giganteus fruiting body. In the present study, P. giganteus is cultivated in a climate chamber, and comparative transcriptome, proteome, and nutritional analysis of P. giganteus fruiting bodies were performed. Our results revealed that Cytochrome P450 monooxygenases and hydrophobin proteins play important roles during the differentiation in the elongation stage. Later, carbon metabolism dominate the fruiting body metabolism and genes related to the carbohydrate metabolic process, glycolytic process, and gluconeogenesis were up-regulated in the mature fruiting bodies. The up-regulation of carbohydrate substrates utilization CAZymes genes and inconsistent protein expression in pileus indicated a reverse transportation of mRNA from the fruiting body to vegetative mycelia. In addition, protein concentration in the pileus is higher than that in the stem, while the stem is the major nitrogen metabolic and amino acid synthetic location. The integrated transcriptomic, proteomic, and nutritional analysis indicated a two-way transportation of substrates and mRNAs in P. giganteus. Stem synthesizes amino acids and transported them to pileus with reducing sugars, while pileus induces the expression of substrate degradation mRNA according to the needs of growth and development and transports them in the other direction.